Meningkatkan Manajemen Sumber Daya Manusia di PT Indonesia Kyouei Saikyu Kawasan Industri KIIC Kabupaten Karawang - Febriyan Muliany (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study aims to analyze and enhance the effectiveness of Human Resource Management (HRM) at PT Indonesia Kyouei Saikyu, particularly in aspects of employee productivity, retention, and the company's competitive edge. This research employs a qualitative descriptive approach with a case study method, involving in-depth interviews, participatory observation, and document analysis. The findings indicate that improving employee retention strategies, optimizing training programs, and adopting technology in performance management positively impact employee productivity and loyalty. Additionally, strengthening organizational culture and structured career development have been proven to enhance job satisfaction and employee commitment to the company. The implementation of these recommendations is expected to help PT Indonesia Kyouei Saikyu achieve a stronger competitive advantage in an increasingly competitive global market. Therefore, the company can more effectively manage its HR assets, ensuring sustainability and long-term growth.